2018
DOI: 10.1016/j.devcel.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

APC Inhibits Ligand-Independent Wnt Signaling by the Clathrin Endocytic Pathway

Abstract: Adenomatous polyposis coli (APC) mutations cause Wnt pathway activation in human cancers. Current models for APC action emphasize its role in promoting β-catenin degradation downstream of Wnt receptors. Unexpectedly, we find that blocking Wnt receptor activity in APC-deficient cells inhibits Wnt signaling independently of Wnt ligand. We also show that inducible loss of APC is rapidly followed by Wnt receptor activation and increased β-catenin levels. In contrast, APC2 loss does not promote receptor activation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(104 citation statements)
references
References 56 publications
(83 reference statements)
9
92
1
Order By: Relevance
“…While this can be explained in part by a decrease in ß-catenin (CTNNB1) mRNA expression (data not shown), the total cellular protein level of ß-catenin decreased more than its CTNNB1 mRNA, suggesting that ß-catenin protein degradation is enhanced. This is in line with findings from Saito-Diaz et al (Saito-Diaz et al, 2018), which suggest that LRP6 associates with the ß-catenin destruction complex in the absence of a Wnt ligand, partially inhibiting its activity. Thus the loss of LRP6 allows the destruction complex to be more active, decreasing overall ß-catenin protein.…”
Section: Lrp6 Modulates Wnt Signaling Levels In Apc-mutant Colon Cancersupporting
confidence: 92%
See 1 more Smart Citation
“…While this can be explained in part by a decrease in ß-catenin (CTNNB1) mRNA expression (data not shown), the total cellular protein level of ß-catenin decreased more than its CTNNB1 mRNA, suggesting that ß-catenin protein degradation is enhanced. This is in line with findings from Saito-Diaz et al (Saito-Diaz et al, 2018), which suggest that LRP6 associates with the ß-catenin destruction complex in the absence of a Wnt ligand, partially inhibiting its activity. Thus the loss of LRP6 allows the destruction complex to be more active, decreasing overall ß-catenin protein.…”
Section: Lrp6 Modulates Wnt Signaling Levels In Apc-mutant Colon Cancersupporting
confidence: 92%
“…The loss of LRP6 affects the stability of ß-catenin due to the release of the destruction complex from the plasma membrane. (Saito-diaz et al, 2018) J. Scratch assay of SW620 Cas9 versus LRP6KO shows a significant difference in cell motility only after 48 hours, suggesting with a more dramatic Wnt inhibition, there is an increase in cell motility.…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Wnt activation is known to induce endocytosis of the receptor complex (11,12). We confirmed that Lrp6 endocytosis was observed in SW480, a colon cancer cell line in which the absence of APC triggered, and APC reconstitution inhibited, Wnt signaling and Lrp6 endocytosis (SI Appendix, Movie S1); this is in agreement with recent results showing that APC is a major regulator of endocytosis (16,29). As expected for regulators of Lrp6 endocytosis, the Wnt antagonists Dkk1 (30) or Bighead (31) induced endocytosis of Lrp6-APEX2 into large vesicle clusters in the cytoplasm next to the nuclear bay region, where the lysosomal system is located Fig.…”
Section: Lrp6-apex2 Receptor Fusion Is Active In Wnt Signalingsupporting
confidence: 91%
“…Specifically, whereas intact APC inhibits ligandindependent clathrin-mediated endocytosis, APC mutation in colorectal cancer allows augmented β-catenin signaling via increased endocytic trafficking. 42 Alternatively, increased vesicle acidification in colorectal cancer has been shown to promote APC degradation via the endolysosomal pathway, leading to enhanced β-catenin signaling. 43 Nevertheless, the roles of endosome trafficking and Wnt/β-catenin signaling in oral dysplasia remain unexplored, and hence, our findings showing that increased Rab5 activity, endosomal sequestration of the destruction complex, and nuclear localization of β-catenin, contribute to understanding the relevance of this mechanism in early oral lesions.…”
Section: Discussionmentioning
confidence: 99%